Comparative Analysis of Return, Net Flow and Expense Ratio of Selected Open – Ended Mutual Fund Schemes - Dr. Bhuwan Chandra Melkani; Vineet Pathak (International Journal of Engineering and Management Research, 2022)
Mutual fund industry in India has revealed a significant growth since its inception in the year 1963 even then it is far behind the developed as well as most of the emerging markets operating globally. One of the most important functions of the mutual fund industry is to mobilize the savings of the households and park their small savings in capital assets with the aim to provide them better risk adjusted return. The present study has tried to compare the return, net flow and expenses ration of the broadly classified mutual funds i.e. large cap, mid cap and small cap. Data on the selected variables have been taken for the period of 11 years from 2011 to 2021 and analyzed using one way anova. Outcomes of the study revealed that the mean return of small cap funds is highest followed by mid cap and large cap. On the basis of the outcomes this study concluded that in present there is no significant difference among the return of large cap, mid cap and small cap funds. For the variable net flow this study revealed that the average net flow of large cap funds is highest followed by small cap and mid cap funds. On the basis of the outcomes this study concluded that there is a significant difference among the net flow of large cap, mid cap and small cap funds. Average expenses of large cap funds are found lowest followed by small cap and mid cap funds. On the basis of the outcomes this study concluded that there is a significant difference among the expenses ratio of large cap, mid cap and small cap funds.